The Impact of Carrying Heavy Bags on Elementary School Students: Challenges and Solutions in the Digital Era - Mahadi Pardede; A. Sobandi (South Sulawesi Education Development (SSED), 2024)
This literature review examines the impact of carrying heavy backpacks on primary school students and explores possible solutions in the digital age. Through a systematic analysis of 30 selected studies published between 2013 and 2024, this review finds that excessive backpack weight significantly affects students' physical health, psychological well-being and social development. The key results show a correlation between the weight of the bag more than 10% of the body weight of the students and an increased risk of musculoskeletal problems, decreased motivation to learn and reduced participation in the social activity. Innovative solutions such as the use of digital technologies, the reformulation of school curricula and the improvement of school infrastructure show that they can solve this problem. This review highlights the importance of a holistic approach involving all stakeholders to address the challenge of heavy bags in the digital age.